Ginseng soluble dietary fiber can regulate the intestinal flora structure, promote colon health, affect appetite and glucolipid metabolism in rats - Mei Hua; Meiling Fan; Zhiman Li; Jiyue Sha; Shanshan Li; Yinshi Sun (Journal of Functional Foods, 2021)
In this study, the effects of ginseng water-soluble dietary fiber (ginseng-SDF) on metabolism, appetite and colon health in rats were investigated. The results showed that ginseng-SDF could improve the glucolipid metabolism, especially in the triglyceride levels. Ginseng-SDF also increased satiety and delayed gastric emptying by regulating the appetite hormone levels as ghrelin, glucagon-like peptide-1, peptide YY, and cholecystokinin. In addition, ginseng-SDF improved intestinal structures and enhanced fecal short-chain fatty acids concentrations (especially acetic acid and butyric acid). More importantly, ginseng-SDF affected the abundance of Firmicutes and Bacteroides, and significantly promoted the proliferation of probiotics and cellulolytic bacteria such as Lactobacillus, Bifidobacterium and Ruminococcus_bromii. Among them, Bifidobacterium pseudolongum, Lactobacillus helveticus and R. bromii were correlated with blood glucose and blood lipid levels. These results suggested that ginseng-SDF could alter the intestinal flora structure, promote colon health, and ultimately have a positive impact on glucolipid metabolism and energy homeostasis.